Geographical and Ethical Integration in Climate Change Mitigation: A Case Study of Agricultural Land in Lembang, West Java - Helga Alvita; Yedi Purwanto; Abdul Aziz (Journal of Geosciences and Environmental Studies, 2026)
Climate change has become a real threat to sustainable living, driven by rising greenhouse gas (GHG) emissions from human activities, including agriculture. This study aims to estimate GHG emissions in the agricultural sector in Lembang subdistrict, an area with high agricultural cultivation intensity, and formulate mitigation strategies through an Islamic ethical approach. The study uses a descriptive-qualitative method, focusing on GHG emissions from the use of inorganic fertilizers and soil cultivation. Estimates of agricultural land area and distribution in each village were analyzed using QGIS. The estimation calculations refer to the Tier-1 method of the 2006 IPCC (Intergovernmental Panel on Climate Change) and the 2012 Ministry of Environment's National Greenhouse Gas Inventory Guidelines. Input data for mitigation strategies was obtained through interviews with farmers associated with the Walungan Foundation in Suntenjaya village. Based on the results of the calculation, GHG emissions in the Lembang subdistrict were estimated at 2,404.46 tons of CO2e per year, arising from the main agricultural commodities: tomatoes, cayenne pepper, and curly peppers. The highest estimated GHG emissions were from the villages of Suntenjaya, Cikidang, and Pagerwangi, which also had more extensive field/farmland than other villages. Based on these findings, a mitigation strategy was formulated by reducing fertilizer use in agriculture. Based on these findings, a mitigation strategy was formulated by reducing agricultural processes in terms of excessive urea fertilizer use, reducing intensive soil cultivation, and, from an ethical perspective, providing assistance and guidance to farmers with a spiritual and environmental awareness approach to maintaining the balance of nature.